Active impedance‐based single‐phase hybrid active power filter. Issue 9 (13th June 2019) - Lemma, Bisrat Gezahegn; Liao, Minfu
Abstract : This article presents a single‐phase hybrid active power filter (1pSHAPF) containing a small rated active power filter connected in series with a single‐tuned inductive‐capacitive (LC) passive filter. Single‐phase nonlinear loads are increasing alarmingly in the distribution system. This is because the devices are gaining attraction for applications in information technology, emerging electric vehicle technology, and interfacing for power grids. However, nonlinear loads are common source of harmonics and contribute unpleasant conditions for the power systems. In the proposed control, a single‐phase hybrid active power filter was actively adjusted to form multiple active short circuits for characteristic harmonic. Load harmonic current easily diverted into filter path and harmonic voltages eliminated from the bus due to the active short circuit formed at the bus. The LC passive filter blocked 70% of the maximum fundamental bus voltage. This allows us to use lower DC‐link voltage hence reduces switching loss and investment for inverters. The detailed design procedures and their realization on TMS320F28335 DSP are analyzed and presented using PSIM and MATLAB/Simulink environments. The performances of the proposed controller are evaluated using diode rectifiers with resistance‐capacitance (RC) and resistance‐inductance (RL) loads. The results showed good harmonic voltage damping, current harmonic reduction (from 60.86 to 9.4%), and power factor correction. Therefore, the proposed controller can be taken as a solution to extend the hybrid active power filter (HAPF) tuned into multiple harmonic frequencies. This research has a practical benefit for power quality (PQ) compensation in the case of a single‐phase smart grid. © 2019 Institute of Electrical Engineers of Japan. Published by John Wiley & Sons, Inc.